Professional Standards for VET Teachers and Additional Functions with Essential Knowledge and Understanding - World Bank (World Bank, Washington, DC, 2021)
The standards contained in this publication address the role of the Vocational Education and Training (VET) Teacher in Georgia. The standards have been developed in close collaboration with key stakeholders in the country from the public and private sectors. The project was supported by the UK government’s Good Governance Fund and implemented by a local and international World Bank team guided by a Steering Committee led by the Ministry of Education, Science, Culture and Sport (MESCS). The standards presented in this document are organized under six Key Areas which derive from Functional Analysis. These are summarized as follows: analysis and planning, preparing the learning environment, leading the learning process, assessing the achievements of VET students, establishing ethical and effective working relationships, and maintaining and improving quality and continuing professional development.